10‐2: Study of an Ultra‐fast Photonic Soldering Technology without Thermal Damage in Display Module Package. Issue 1 (28th June 2021) - Ho, Ming-jaan; Li, Yanlu; Liu, Likun; Li, Yang; Gao, Chunlan
Abstract : An ultra‐fast photonic soldering approach to be introduced in the display module package, which has great advantages in soldering low temperature and heat sensitive components, was demonstrated. The soldering and heat conduction process was verified. As a result, flexible substrate was successfully interconnected on the display panel by photonic soldering.